IFHTSE Global 21: heat treatment and surface engineering in the twenty-first century Active screen plasma nitriding and nitrocarburising of steels: an overview. (September 2014) - Spies, H-J.; Burlacov, I.; Börner, K.; Biermann, H.
Abstract : Active screen plasma nitriding (ASPN) is a novel nitriding method, which has been demonstrating its growing commercial recognition for many years now. A characteristic feature of the ASPN process is a repositioning of the plasma source from the component surface towards a screen surrounding the batch. Application of independent bias power to the metal substrate provides an additional control of the flux of energetically active species directed to the components' surface. The advanced plasma technology overcomes a number of limitations of the conventional DC diode plasma nitriding. Both plasma assisted nitriding methods are very comparable regarding the equipment, which makes the ASPN method highly commercially competitive. Owing to the large number of independent process parameters in the ASPN process the structure of the nitrided layer with defined case characteristics can be effectively controlled to fulfil the application requirements. Process gas composition, working pressure and bias activation are the important process parameters. Controlled plasma nitriding and plasma nitrocarburising with the active screen provides a unique possibility to produce the whole spectrum of the nitrided layers beginning from the compound layer free surface, through the γ′- and ϵ-phase layer, up to the ϵ-carbonitrided layer.